Response of carbon, nitrogen, and phosphorus in leaves of different life forms to altitude and soil factors in Tianshan wild fruit forest - Jia, Xiande; Wu, Limei; Ren, Jiamin; Peng, Xinyang; Lv, Haiying (Frontiers in Ecology and Evolution, 2024)
The ecological stoichiometric ratio of carbon, nitrogen, and phosphorus is an important index to understand the utilization and distribution of plant nutrients. To explore the response of leaf carbon, nitrogen, phosphorus content, and stoichiometric ratio of different life forms of plants to altitude and soil physical and chemical properties in the wild fruit forest in the Tianshan Mountains of Yili, Xinjiang, the leaves and soil samples of different life forms of plants were collected at different altitudes ( 1100 1700 m ) in the Guozigou of the wild fruit forest in the Tianshan Mountains of Yili, Xinjiang. The contents and ratios of carbon, nitrogen, and phosphorus of the leaves, as well as the physicochemical properties of the soil, were determined. The results showed the following. The three life forms plants in the study area showed that the coefficient of variation of leaf carbon content was the smallest and the distribution was the most stable, while the coefficient of variation of carbon-nitrogen ratio was the largest. Altitude had a significant effect on the carbon, nitrogen, and phosphorus contents of different life-form plants, among which the leaf nitrogen content of trees, shrubs, and herbs increased significantly with altitude (P < 0.01), the leaf phosphorus content of trees increased significantly with altitude (P < 0.01), and the leaf C ∶ N of the three life-form plants decreased significantly with altitude (P < 0.01). The C ∶ P of the arbor decreased significantly with altitude , and the N ∶ P of shrub and herb leaves increased significantly with altitude . Soil organic carbon and soil moisture content were the main environmental factors affecting the changes of carbon, nitrogen, and phosphorus in leaves of arbors, and nitrate nitrogen was the main environmental factor affecting the changes of carbon, nitrogen, and phosphorus in leaves of shrubs. Available phosphorus affected the changes of carbon, nitrogen, and phosphorus in the leaves of herbaceous plants. The results provide new insights into community-level biogeographical patterns and potential factors of leaf stoichiometry among plant life forms.-level biogeographical patterns and potential factors of leaf stoichiometry among plant life forms.